Trastuzumab Rechallenge in HER2-Positive Metastatic Breast Cancer: A Promising Strategy for Enhanced Progression-Free Survival Post Ado-Trastuzumab Emtansine Progression - Yunus Emre Altıntaş; Oğuzcan Kınıkoğlu; Anıl Yıldız; Deniz Işık; Uğur Özkerim; Sıla Öksüz; Tuğba Başoğlu Tüylü; Heves Sürmeli; Nedim Turan; Hatice Odabaş (Medicina)
Background and Objectives: Metastatic breast cancer (MBC), particularly the HER2-positive subtype, represents a significant clinical challenge, with approximately 20–25% of breast cancer cases demonstrating HER2 overexpression. Trastuzumab, a monoclonal antibody targeting HER2, has significantly improved outcomes in these patients. However, progression after second-line treatments such as trastuzumab emtansine (T-DM1) necessitates exploring subsequent therapeutic options. This study aims to compare the efficacy of trastuzumab plus gemcitabine (GT) with lapatinib plus capecitabine (LC) as third-line treatments in HER2-positive MBC post-T-DM1 failure. Materials and Methods: This retrospective study included 98 HER2-positive MBC patients treated between 2017 and 2023 who progressed after T-DM1. Patients were divided into two groups: 21 received GT, and 28 received LC. Key endpoints included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and adverse events. Statistical analyses were performed using SPSS 26.0, with Kaplan–Meier survival curves, log-rank tests, and Cox proportional hazards models. Results: Median PFS was significantly longer in the GT group (9.5 months) compared to the LC group (4.3 months, p = 0.02). OS was also higher for GT (22.1 months vs. 10.0 months, p = 0.02). ORR favored the GT group (33.3% vs. 10.7%, p = 0.046), and progressive disease was more common in the LC group (57.1% vs. 33.3%, p = 0.022). The safety profile showed higher rates of diarrhea in the LC group, but both regimens were generally well tolerated. Conclusions: Trastuzumab re-challenge with gemcitabine demonstrated superior PFS, OS, and ORR compared to lapatinib plus capecitabine, suggesting it may be a more effective third-line therapy in HER2-positive MBC patients who have progressed after T-DM1. Further prospective studies are needed to confirm these findings and optimize treatment sequencing.